Inhibition of the Initiation of Cellular DNA Synthesis After Reovirus Infection - Cox, Donald C. (1974)
The synthesis of cellular DNA was measured in synchronized L cells after reovirus infection. Initiation of the synthetic phase of the cell cycle was completely inhibited in cells infected 8 h before the beginning of DNA synthesis.